2017
DOI: 10.1007/978-94-024-1079-2_72
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Taurine Against PFOS-Induced Neurotoxicity in PC12 Cells

Abstract: As a new member of persistent organic pollutants, the potent neurotoxicity of perfluorooctane sulfonates (PFOS) found in epidemiological studies and laboratory research has drawn increasing attention around the world. Previous studies showed that apoptosis driven by oxidative stress and autophagy were both observed in PFOS-induced toxicity. Taurine has been demonstrated to exert potent protections against oxidative stress as an efficient antioxidant. Whether taurine could protect against the PFOS neurotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…5A). In concordance with our results, around 40% reduction in viability in PC12 cells after 24 h exposure to 250 μM PFOS was also reported in a recent study by Li et al (2017). A possible explanation for the lower PFOS-induced toxicity in PC12 cells may be their reported lack of expression of functional NMDA-R (Edwards et al, 2007), or as discussed previously the presence of serum in the medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5A). In concordance with our results, around 40% reduction in viability in PC12 cells after 24 h exposure to 250 μM PFOS was also reported in a recent study by Li et al (2017). A possible explanation for the lower PFOS-induced toxicity in PC12 cells may be their reported lack of expression of functional NMDA-R (Edwards et al, 2007), or as discussed previously the presence of serum in the medium.…”
Section: Discussionsupporting
confidence: 93%
“…5B). Li et al (2017) found an increase in the production of reactive oxygen species (ROS) in PC12 cells, after PFOS exposure, which was reduced by cotreatment with taurine treatment. In the present study we also found that a mixture of the anti-oxidants vitamin E and C protected against PFOS-induced effects on viability (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…To further examine the changes of lysosomal function caused by 27-OHC treatment, LTR was used to label lysosomes in live cells. As an acidotropic probe, the decreased LTR fluorescence reflected both a rise in pH of lysosomal and a reduction in number of lysosomes (Li et al, 2017). Treatment with 27-OHC markedly reduced the fluorescence intensity, indicating that 27-OHC treatment reduced intracellular acidic components and the number of lysosome (Figure 2E), and the possibility of LMP occurrence in SH-SY5Y cells and C6 cells.…”
Section: Resultsmentioning
confidence: 99%
“…It also attenuated rotenone-induced catalase and lipid peroxidation levels [87]. In PC12 cells, treatment with taurine produced protection against toxic agent-induced degeneration [[88], [89], [90]]. Taurine also restored reduced Bcl-2 expression in an H 2 O 2 -induced model.…”
Section: Therapeutic Potential Of Taurine Against Neurological Disordersmentioning
confidence: 99%
“…Against perfluorooctane sulfonate-induced degeneration, administration of taurine also displayed protective activity in PC12 cells. Taurine reduced reactive oxygen species (ROS) production and attenuated perfluorooctane sulfonate-induced increases in autophagy and apoptosis [89]. Moreover, treatment significantly reversed the decrease in viability, oxidative stress and abnormal autophagy in PC12 cells exposed to BDE 209 [90].…”
Section: Therapeutic Potential Of Taurine Against Neurological Disordersmentioning
confidence: 99%